Vector basic training : a systematic creative process for building precision vector artwork. - Glitschka, Von, ....- (Berkeley : New Riders, 2011)
Listen up, designers, and wipe those grins off your faces! It's time to get serious about your design work. For too long you've allowed yourself to go soft, relying on your software to do all of your creative work for you. This book will NOT show you how to use every tool and feature in Adobe Illustrator. This book WILL, however, teach you the importance of drawing out your ideas, analyzing the shapes, and then methodically building them precisely in vector form using the techniques explained in this book. In "Vector Basic Training," acclaimed illustrative designer Von Glitschka takes you through his systematic process for creating the kind of precise vector graphics that separate the pros from the mere toolers. Along the way, he'll whip your drawing skills into shape and show you how to create elegant curves and precise anchor points for your designs. Between the book and the video tutorials on the included DVD, you'll be ready for active creative duty in zero hundred hours or less. In "Vector Basic Training," you'll learn: The tools and shortcuts that make up a design pro's creative armamentHow to use "The Clockwork Method" to create accurate curves every time When and where to set just the right number of anchor points for any design How to build shapes quickly using basic Illustrator tools and plug-insTechniques for art directing yourself so that your work gets the response you desireWhy symmetry is your friend and how to use it effectively in your designs"To get the most out of this book it is recommended that you have Adobe Illustrator CS4 or higher." On the DVD-ROM Von Glitschka reports for duty in over four hours' worth of video tutorials that walk you through all of the techniques explained in the book. Also included: downloadable art files you can use to follow along on your own and deconstruct samples shown in the book.